2011
DOI: 10.1111/j.1464-410x.2011.10629.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for advanced renal cell cancer (RCC): a Cochrane systematic review of published randomised trials

Abstract: What's known on the subject? and What does the study add? Targeted agents have greatly changed the therapeutic landscape in RCC. A substantial number of trials have been published in recent years. The current review summarises and analyses the available data to date. OBJECTIVE To estimate the effects of drugs with molecular targets on patients with advanced renal cell cancer (RCC). PATIENTS AND METHODS MEDLINE, EMBASE, and the Cochrane Collaboration Library were systematically searched on‐line through to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
172
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(174 citation statements)
references
References 43 publications
0
172
0
2
Order By: Relevance
“…The results of the sideby-side TKI studies determining potency, selectivity, and efficiency are shown in Table 1. The inhibitor names, along with structural features and clinical endpoints, are also shown (1,2,22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the sideby-side TKI studies determining potency, selectivity, and efficiency are shown in Table 1. The inhibitor names, along with structural features and clinical endpoints, are also shown (1,2,22).…”
Section: Resultsmentioning
confidence: 99%
“…axitinib | pazopanib | sorafenib | sunitinib | tivozanib T he VEGF receptor (VEGFR) tyrosine kinases (TKs) are the clinically validated drug target of four structurally diverse TK inhibitors (TKIs) that have been approved in the renal cell carcinoma (RCC) setting (1,2). The clear cell histology subtype of RCC is molecularly linked to the VEGF signaling axis by virtue of the ∼90% incidence of Von Hippel-Lindau (VHL) dysregulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed studies were published during 2007-2011, including five full text articles, 24 research abstracts and one HTA report. [9]. b [10].…”
Section: Cost-effectiveness Studies Of New Therapies For Mrccmentioning
confidence: 99%
“…23,24 Currently available treatment options for advanced RCC, that is, tyrosine kinase inhibitors (TKI) or mammalian target of rapamycin (mTOR) inhibitors, tackle disease stabilization without a curative intent. 25,26 In our model, carefully titrated T-cell infusions provided tumor-free survival without GVHD for more than 50% of the animals. High transplant-related mortality has limited to use of allogeneic HSCT for patients with RCC.…”
Section: Discussionmentioning
confidence: 95%